Comparing calibration coefficients constrained from early to recent macroseismic and instrumental earthquake data in Greece and applied to eighteenth century earthquakes - V. Kouskouna; Kaperdas, V.; Sakellariou, N. (Journal of Seismology, 2020)
The purpose of this paper is to determine calibration constants of instrumental Greek earthquakes in order to calculate the basic seismic parameters of historical earthquakes (magnitude, epicenter, focal depth) via macroseismic data. Two different approaches are adopted for calibration procedure. The first implements the macroseismic estimation of earthquake parameters (MEEP procedure) and is based on macroseismic data points (MDPs). The second approach calculates macroseismic magnitude based on isoseismal areas, using both linear and multiple regression techniques. The datasets used for analysis comprise of 121 instrumental earthquakes with 7247 MDPs and 123 isoseismal maps. Validation of the results is performed using six instrumental earthquakes in order to verify the calibration parameters. Finally, calibration constants are successfully applied for parameters calculation of eight eighteenth century events. Thus, the application of the results to historical earthquakes contributes to the improvement of the seismic picture of Greece.